Content and source analysis of newspaper items about Māori issues: Silencing the ‘natives’ in Aotearoa? - Sue Abel (Asia Pacific Network, 2014)
This article reports on a content analysis of newspaper items from Aotearoa/New Zealand about Māori issues, focusing on level of coverage, topics and sources. Results from analysis of a representative sample of news items from six months over 2007-2008 were compared with two previous pilot studies in 2004 and early 2007. The study found that the mass media covered Māori stories at very low rates, worked a narrow range of topics and prioritised Pākehā sources over Māori, even in articles specifically about Māori issues. The authors sketch an indigenous theory of media news processes and relate these findings to already published thematic and discourse analyses of the materials from the same database to illustrate the roles of mass media coverage in the dynamics of national life in Aotearoa.